(untitled) (IJOVTECH, 2026)
This study investigates the role of virtual reality (VR) in enhancing experiential learning among diverse student populations in Ebonyi State, Nigeria, a region characterized by socioeconomic challenges and educational disparities. Drawing on Kolb's experiential learning theory, the research employs a mixed-methods approach to examine how VR interventions can bridge gaps in traditional education by providing immersive, interactive experiences that cater to varied learning styles and cultural backgrounds. The primary data collection involved a quasi-experimental design with 250 secondary school students from urban and rural areas in Ebonyi State, selected through stratified sampling to ensure representation across gender, ethnicity, age, and socioeconomic status. Participants were divided into experimental and control groups, with the experimental group engaging in VR-based simulations for subjects like biology and history, while the control group used conventional methods. Pre- and post-intervention assessments measured knowledge retention, engagement levels, and self-efficacy through standardized tests, surveys, and semi-structured interviews. Results indicated significant improvements in experiential learning outcomes for the VR group, with a 28% increase in knowledge retention and higher engagement scores, particularly among female and rural students. Demographic analysis revealed that 55% of participants were from low-income households, 60% Igbo ethnicity, and ages ranging from 14 to 18 years. Challenges such as limited infrastructure and digital literacy were noted, but VR's potential to democratize education in diverse settings was evident. The findings underscore VR's efficacy in fostering inclusive experiential learning, aligning with sustainable development goals for quality education. Recommendations include policy integration of VR in Nigerian curricula and teacher training programs. This study contributes to the discourse on technology-enhanced education in developing contexts, highlighting VR's transformative impact on experiential pedagogy.